2019
DOI: 10.1007/s00023-019-00839-7
|View full text |Cite
|
Sign up to set email alerts
|

The Hessian in Spin Foam Models

Abstract: We fill one of the remaining gaps in the asymptotic analysis of the vertex amplitudes of the Engle-Pereira-Rovelli-Livine (EPRL) spin foam models:We show that the hessian is nondegenerate for the stationary points that corresponds to geometric nondegenerate 4 simplices. Our analysis covers the case when all faces are spacelike.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Numerical investigations in [16] showed that it is non-degenerate, and that H + = H − , for various critical configurations considered. An analytic proof that the Hessian in non-degenerate on a dense set of critical points was then given in [57]. 11 With this information and the results of the previous analysis we obtain the following asymptotic formulas.…”
Section: Asymptotic Formulaementioning
confidence: 90%
See 1 more Smart Citation
“…Numerical investigations in [16] showed that it is non-degenerate, and that H + = H − , for various critical configurations considered. An analytic proof that the Hessian in non-degenerate on a dense set of critical points was then given in [57]. 11 With this information and the results of the previous analysis we obtain the following asymptotic formulas.…”
Section: Asymptotic Formulaementioning
confidence: 90%
“…For its determinant one will in general have to be content with numerical evaluations, which we did not attempt here. If one is not interested in the overall phase, the calculation can be simplified using a reduced Hessian like in [57]. It would of course be useful to extend the analytic proof of non-degeneracy of the 4-simplex Hessian presented in [57], but this would require further work.…”
Section: General Asymptotic Formulaementioning
confidence: 99%